OPTIMIZATION OF FERMENTATION CONDITIONS FOR COLLECTING OF BACILLUS SUBTILIS NT1 BIOMASS USED IN CANNA EDULIS. KER PROCESSING WASTEWATER TREAMENT - Nhu Ngoc, Nguyen; Van Cach, Nguyen; Dinh Giap, Trinh (Journal of Forestry Science and Technology, 2017)
Canna edulis. Ker processing craft villages in rural area of Vietnam are developing rapidly thus helping local people to create high-income jobs. However, large amount of untreated waste water and solid waste have been causing serious environmental pollution. Strain Bacillus subtilis NT1, isolated from wastewater of Canna edulis. Ker processing craft village, has proven to be capable of handling wastewater. In order to produce microbial products for wastewater treatment in large scale, fermentation conditions for B. subtilis NT1 were optimized by submerged fermentation method. By surveying influenced factors and optimization by the Box-Behnken method, optimal condition for B. subtilis NT1 growth was determined at 8.0 (g/l) glucose, 7.0 (g/l) peptone, shaking speed 195 rpm, 30°C, the inoculum rate of 5% (v/v) and initial pH of 6. After 24 hours biomass obtained was 11.98 LogCFU/ml.